2018
DOI: 10.1111/tpj.14081
|View full text |Cite
|
Sign up to set email alerts
|

Two R2R3‐MYB proteins are broad repressors of flavonoid and phenylpropanoid metabolism in poplar

Abstract: The phenylpropanoid pathway leads to the production of many important plant secondary metabolites including lignin, chlorogenic acids, flavonoids, and phenolic glycosides. Early studies have demonstrated that flavonoid biosynthesis is transcriptionally regulated, often by a MYB, bHLH, and WDR transcription factor complex. In poplar, several R2R3 MYB transcription factors are known to be involved in flavonoid biosynthesis. Previous work determined that poplar MYB134 and MYB115 are major activators of the proant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 66 publications
(112 reference statements)
5
93
0
Order By: Relevance
“…Such differential regulation of the triterpenoid pathway has recently been reported in W. somnifera by the WsWRKY1 [30], in tomato by the GAME9 [46] In general, one target genes were regulated by several TFs, in the same way, one TF also involved in multiple biosynthetic step. Such result was also reported by previous observations [48,49]. The fact that CiMYB42-transgenics effectively altered limonoids accumulation give us a better understanding of the molecular mechanisms that control the citrus limonoids biosynthesis.…”
Section: Discussionsupporting
confidence: 88%
“…Such differential regulation of the triterpenoid pathway has recently been reported in W. somnifera by the WsWRKY1 [30], in tomato by the GAME9 [46] In general, one target genes were regulated by several TFs, in the same way, one TF also involved in multiple biosynthetic step. Such result was also reported by previous observations [48,49]. The fact that CiMYB42-transgenics effectively altered limonoids accumulation give us a better understanding of the molecular mechanisms that control the citrus limonoids biosynthesis.…”
Section: Discussionsupporting
confidence: 88%
“…It has been demonstrated that the phenylpropanoid and flavonoid biosynthesis pathways are regulated by different TF classes, such as MYB, WRKY, NAC, and bHLH, through modulating the expression of the related structural genes. Among these TFs, MYB-bHLH-WD40 repeat (MBW) ternary complexes have been illustrated to be one of the most important regulatory components that are involved in phenylpropanoid and flavonoid biosynthesis [52][53][54][55][56]. To date, certain MBW component genes that regulate flavonoid biosynthesis have been identified in tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…In the poplar genome, 192 R2R3 MYB transcription factors have been predicted (Wilkins et al ., ), but only a small number of MYB members, including MYB134 (Mellway et al ., ), MYB182 (Yoshida et al ., ), MYB119 (Cho et al ., ), MYB57 (Wan et al ., ), MYB115 (James et al ., ; Wang et al ., ), PtrMYB012 (Kim et al ., ), and MYB165 and MYB192 (Ma et al ., ), have been found to regulate the flavonoid biosynthetic pathway. In the study reported herein, we isolated and characterized the poplar transcription factor MYB6, which shows high homology in amino acid sequences to other MYB5‐like transcription factors.…”
Section: Introductionmentioning
confidence: 99%